Evaluation of professional knowledge and attitudes on dementia patient care: a trans-cultural adaptation of an evaluation instrument - Gislaine Desani da Costa; Rosely Almeida Souza; Cintia Hitomi Yamashita; Juliane Cibelle Ferreira Pinheiro; Márcia Regina Martins Alvarenga; Maria Amélia de Campos Oliveira (SciELO, 2015)
Objective To describe the trans-cultural adaptation of the evaluation instrument entitled Atenció Sanitària de Les Demències: la visió de L' Atenció Primarià from Catalan into versions in Portuguese for doctors and nurses. This study evaluates the knowledge and perspectives of these professionals in their treatment of patients diagnosed with dementia in cases of primary care. Method The adaptation followed internationally accepted rules, which include the following steps: translation, synthesis, back-translation, revision by a committee of specialists, and a test run with 35 practicing doctors and 35 practicing nurses in Brazil's Family Health Strategy (Estratégia Saúde da Família, or ESF in Portuguese). Results The translation, synthesis, and back-translation steps were performed satisfactorily; only small adjustments were required. The committee of specialists verified the face validity in the version translated into Portuguese, and all of the items that received an agreement score lower than 80% during the initial evaluation were revised. In the test run, the difficulties presented by the health care professionals did not reach 15% of the sample, and therefore, no changes were made. Conclusion The Portuguese translation of the instrument can be considered semantically, idiomatically, culturally, and conceptually equivalent to the original Catalan version and is, therefore, appropriate for use in Brazil.